The Theoretical Background of Behavioral Finance and Analysis of Investor’s Behavior in capital market - BENSANIA , Abderrahmane; NAAS , Salah Eddine; BENDOB , Ali (Journal of Excellence for Economics and Management Research, 2017)
This paper highlights on the anomalies in the capital markets, that the traditional financial models have failed to explain, and the extent to which behavioral financial theory (BFT) can explain and understand what is happening in capital markets. The BFT provides a new scientific explanation, on the behavior of investors and pushes them to make investment decisions are not rational and reflected negatively on their investment performance, The study concluded that the BFT provides more reasonable explanations for the anomalies in pricing and a deeper understanding of investment and trading processes in the capital markets. However, despite all the financial behavioral findings and interpretations of capital markets, there is no real uniform theory of behavioral finance, more empirical and mathematical tests.